Hubungan karakteristik maloklusi gigi anterior terhadap status psikososial - Nofrizal, Riko; Cantika Kamilia, Mahdiah (Jurnal Kedokteran Gigi Terpadu, 2025)
Background: Malocclusion is one of the most common oral health problems in Indonesia. Characteristics of malocclusion that can be identified in the anterior teeth include crowding, protrusion, diastema, deep bite, and others. Malocclusion can affect masticatory function, disrupt aesthetics, and influence psychological and social aspects of life. The measurement of the impact of anterior malocclusion characteristics on psychosocial status can be determined using a questionnaire method called the Psychosocial Impact of Dental Aesthetic Questionnaire (PIDAQ). Objective: To determine the relationship between the characteristics of anterior teeth malocclusion and psychosocial status based on PIDAQ among patients at the Orthodontic Clinic RSGM-P FKG Universitas Trisakti. Method: This study is analytical observational research with a cross-sectional design. The sample is patients at the Orthodontic Clinic of the RSGM-P FKG Universitas Trisakti, selected using a consecutive technique. The instrument used was the PIDAQ questionnaire. The collected data were then analyzed through univariate and bivariate analysis using software. Results: The psychosocial status of patients at the Orthodontic Clinic RSGM-P FKG Universitas Trisakti, regarding the characteristics of anterior teeth malocclusion, based on PIDAQ, categorized as good psychosocial status at 51.5%. The results of the contingency coefficient correlation test showed p value=0.846 and a correlation value of 0.333, showing a positive correlation with a weak correlation strength and no clinical significance. Conclusion: The study indicates no correlation between the characteristics of anterior teeth malocclusion and psychosocial status among patients at the Orthodontic Clinic of RSGM-P FKG Universitas Trisakti